Análisis de la estructura y las condiciones del mercado internacional de gas natural (2018)
Natural gas has been an important energy resource in the 21st century, due to the boom in finding sources that offer energy capacity without generating a significant negative impact. This is how natural gas meets conditions that allow its use with ease in the generation of energy (electric, automotive, among others), such as: the ability to compress up to a thousand times its volume or, when combustion, generates only CO2 and water leaving out heavy components as they are left by oil, diesel or coal.